2005
DOI: 10.1029/2004gb002342
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the iron and phosphorus cycles: A three‐dimensional model study

Abstract: [1] We use an ocean circulation, biogeochemistry, and ecosystem model to explore the interactions between ocean circulation, macro-and micro-nutrient supply to the euphotic layer, and biological productivity. The model suggests a tight coupling between the degree of iron limitation in the upwelling subpolar and tropical oceans and the productivity of the adjacent subtropical gyres. This coupling is facilitated by lateral Ekman transfer of macro-nutrients in the surface ocean. We describe a coarse resolution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(225 citation statements)
references
References 111 publications
9
214
2
Order By: Relevance
“…We direct the reader to the online supplemental material of that paper for additional discussion. The most significant change is that the grazing term is now includes variable palatability of phytoplankton and sloppy feeding as treated by Dutkiewicz et al [2005]. Additionally the nitrogen limitation term (equation (A10)) has been slightly modified.…”
Section: Appendix A: Ecosystem Model Parameterizationmentioning
confidence: 99%
“…We direct the reader to the online supplemental material of that paper for additional discussion. The most significant change is that the grazing term is now includes variable palatability of phytoplankton and sloppy feeding as treated by Dutkiewicz et al [2005]. Additionally the nitrogen limitation term (equation (A10)) has been slightly modified.…”
Section: Appendix A: Ecosystem Model Parameterizationmentioning
confidence: 99%
“…Atmospheric delivery of dust is a major source of iron to the ocean, and in this model the dust supply does not change. Though iron is also supplied from depth, in the subtropical regions lateral supplies are more important [Dutkiewicz et al, 2005b]. An increase in biomass occurs in regions where lateral iron supply from upstream becomes higher.…”
Section: Changes At the Biogeochemical Levelmentioning
confidence: 99%
“…Peng & Broecker 1985) indicated a possible reduction in atmospheric CO 2 of 50-100 ppm; however, recent studies with higher resolution three-dimensional models coupled to ecosystem dynamics including iron have suggested that addition of iron is much less efficient (order of 10 ppm) because the other limiting factors of light and grazing become dominant (e.g. Dutkiewicz et al 2005;. The link between nutrient supply and ecosystem dynamics is complex, especially for micronutrients.…”
Section: (B ) Macronutrient Supply From the Deep Oceanmentioning
confidence: 99%
“…In the open oceans, observations have been limited to a purposeful release of phosphate and iron (Rees et al 2006) and to various modelling studies that highlight the intimate and intricate relationships between the various essential elements and the forms in which they are present in the ocean (Dutkiewicz et al 2005;Parekh et al 2005).…”
Section: Efficacy Of Ocean Fertilization For Carbon Sequestrationmentioning
confidence: 99%